Beyond objectivity: interventionist journalism and professional role performance in Global South media landscape - Fahmy, Nagwa; Elhamy, Hossam (Frontiers in Communication, 2025)
This study investigates journalistic interventionism within the diverse media landscape of the Global South. Journalism in these regions sometimes takes an interventionist approach. Understanding this approach necessitates moving beyond Western-centric paradigms that may overlook Global South media’s distinctive historical, political, economic, and sociocultural circumstances. The primary objective of this research is to understand the manifestation of the interventionist journalistic role performance across various Global South countries, examining its overall prominence and the influential factors that affect interventionist role deployment. The study examines interventionist journalism in 16 Global South nations using quantitative content analysis of 59,391 news items from 153 media outlets based on the operationalization framework to measure journalistic role performance within news content. The findings reveal a regional pattern in journalistic role performance, with Latin American journalism displaying a more interventionist orientation. The results further showed a significant negative relationship between sociopolitical constraint and interventionist journalistic role performance, suggesting that levels of interventionist journalism decrease as sociopolitical constraints increase. Results also illuminate how national contexts, economic development levels, and political and press freedom influence interventionist journalistic role performance. These findings have significant implications for media organizations and policymakers, highlighting the need for adaptive strategies considering how organizational and contextual factors shape interventionist-driven journalistic practices.